Monitoring the fishing process in the sea urchin diving fishery of Galicia - Fernández Boán, M. (2013)
The assessment and management of small-scale benthic fisheries requires attention to the spatial structure of stocks and patterns of effort allocation. Spatial information helps in the interpretation of fisheries data, and is required for designing spatially explicit management strategies, often prescribed in the case of benthic fisheries. Monitoring of boats with GPS, combined with port interviews, was evaluated as an approach to investigate the spatial pattern of fishing intensity and catch per unit of effort (CPUE) in the sea urchin (Paracentrotus lividus) diving fishery from Galicia, Spain. Fishing opportunities (FOs), relatively small regions of high fishing intensity, were identified and mapped at a fine scale. New FOs were first visited at an approximately constant rate. Concentration analysis shows that effort intensity was not uniformly distributed within FOs. CPUE did not exhibit a significant trend throughout the season, either at the scale of the aggregated fishery or within individual FOs. Catch per area and area covered per unit of diving time were inversely related, indicating that fishers stay longer in high-density patches. While abundance is the primary driver of effort allocation, other factors contributing to suitability were identified. Based on these results, we discuss realistic options for the monitoring of this and comparable fisheries.